Domingo M. Basso O.P., Un fundamentos de la Moral, Centro de Investigaciones en Etica Biomédica, Buenos Aires, 1990, 267 pp - Casaubon, Juan Alfredo (1991)
Fil: Casaubon, Juan Alfredo. Pontificia Universidad Católica Argentina; Argentina